Pengembangan Pendekatan Matematis dan Penyelesaiannya untuk Reliabilitas Sistem Dengan Distribusi Kegagalan Berbeda - Yoon Mac Kinley Aritonang (Jurnal Rekayasa Sistem Industri, 2023)
The productivity of a company or industry is highly dependent on the performance of the machines or equipment used. Reliability is one measure of machine or equipment performances. In industry, machines usually will form a complex configuration with each component having a different failure distribution. Research has been carried out for three systems installed in parallel where the three systems have different of failure distributions. The failure distribution used is the Normal, Weibull, and Normal Log distribution. Reliability calculations can be accomplished by making the three distributions have a similar shape even if could e the same. The three distributions have their respective parameters whose values ​​will be determined so that there is a similarity in the shape of the three distributions. System reliability od system with parallel configuration can then be calculated.